Serum Phosphorus Might Be a Predictor of Kidney Disease Progression in IgA Nephropathy - Huixian Li; Wanhong Lu; Xinfang Xie; Ying Wang; Xiangyun Dang; Jiping Sun; Hongli Jiang (Karger Publishers, 2023)
Introduction: High serum phosphorus level has been reported to be a risk factor for disease progression in patients with chronic kidney disease, whereas, its role in IgA nephropathy (IgAN) still remains uncertain. This study aimed to investigate the association between serum phosphorus and progression of IgAN. Methods: A total of 247 patients diagnosed with IgAN from 2016.11 to 2019.12 at the First Affiliated Hospital of Xi'an Jiaotong University were retrospectively enrolled in this study. The association between serum phosphorus and kidney disease progression events, defined as 30% estimated glomerular filtration rate (eGFR) decline or kidney failure, was evaluated using Cox models. Results: Serum phosphorus was an independent risk factor for poor renal outcome after adjusting for age, gender, urine protein, MAP, eGFR, hemoglobin, Oxford S and T scores (HR, 2.586; 95% CI, 1.238-5.400, p = 0.011). The addition of serum phosphorus to the reference model containing clinical and pathological variables significantly improved the risk prediction of IgAN progression (C statistic, 0.836; 95% CI, 0.783-0.889) as compared with the reference model (C statistic, 0.821; 95% CI, 0.756-0.886). The ability of serum phosphorus level to predict progression was much stronger in IgAN patients without use of immunosuppression (HR 5.173; 95% CI, 1.791-14.944; p = 0.002). Conclusion: Higher serum phosphorus levels were independently associated with kidney disease progression in patients with IgAN, especially in those without immunosuppression. The addition of serum phosphorus to clinical and pathological data at the time of biopsy significantly improved risk prediction of IgAN progression.